2010
DOI: 10.5424/sjar/2010082-1212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nitrification inhibitors to restrict nitrate leaching in a maize crop irrigated under mediterranean conditions

Abstract: The aim of this paper was to compare dicyandiamide (DCD) and 3,4 dimethylpyrazole phosphate (DMPP) as inhibitors of ammonium oxidation and nitrate leaching after applying fertilizer to a maize (Zea mays L.) crop grown under Mediterranean conditions. The effects of nitrification inhibitors were also compared to those of N fertilization without inhibitors and with split N application. In plots fertilized with ammonium sulphate nitrate (ASN), either DCD or DMPP lengthened ammonium presence in soil and produced lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…The UAN treatment had the greatest total leaching loss of 66% of fertilizer N applied whereas leaching from the UAN‐IN and UAN‐NS were not different from each other and both were significantly lower than that from the UAN treatment but greater than that from PCU. These results are consistent with other studies that also showed reduced NO 3 − leaching with specialized N fertilizers such as polymer‐coated urea, urea with urease or nitrification inhibitors or both inhibitors added compared to conventional N fertilizers (Diez et al, 2010; Zaman et al, 2008). These specialized products are designed to release N more gradually over time than conventional N fertilizers to improve synchrony between soil N availability and crop N demand to minimize N loss.…”
Section: Resultssupporting
confidence: 92%
“…The UAN treatment had the greatest total leaching loss of 66% of fertilizer N applied whereas leaching from the UAN‐IN and UAN‐NS were not different from each other and both were significantly lower than that from the UAN treatment but greater than that from PCU. These results are consistent with other studies that also showed reduced NO 3 − leaching with specialized N fertilizers such as polymer‐coated urea, urea with urease or nitrification inhibitors or both inhibitors added compared to conventional N fertilizers (Diez et al, 2010; Zaman et al, 2008). These specialized products are designed to release N more gradually over time than conventional N fertilizers to improve synchrony between soil N availability and crop N demand to minimize N loss.…”
Section: Resultssupporting
confidence: 92%
“…In a field experiment on a permanent pasture, Zaman et al (2008) found that urea with only urease inhibitor or with both urease and nitrification inhibitors (as in the IU in the current study) reduced NO 3 leaching compared with urea alone. Diez et al (2010) also reported significantly lower NO 3 leaching with the use of DCD with a traditional N source. In the current study, greater NO 3 leaching with PCU than with split-U and the trend for greater NO 3 leaching with IU compared with split-U were most likely due to better synchrony of the N application with crop demand for split-U.…”
Section: Nitrate Leachingmentioning
confidence: 91%
“…and other 2 NO − oxidizing microorganisms. In our experiment, we noticed that the rate of 4 NH + disappearance did not correspond to the rate of 3 NO − formation, suggesting that ATS led to the stabilization of N-4 NH + , and thus delaying the production of nitrate [51] [52]. In addition, our results are in accordance with those reported by Al Kanani et al [53] who attributed the non-concomitant 4 NH + to 3 NO − conversion to the accumulation of nitrite, adversely affecting the amount and the activity of soil microorganisms, thus retarding nitrification…”
Section: Influence Of Ats On Nitrification In Untreated or In Urea Trmentioning
confidence: 99%